Islam, Securitization, and Secularism in Post-Soviet Kazakhstan: Negotiating Identity and State Policy - Sikhimbayeva, Damira; Zhanabayeva, Dinara; Toktarov, Yermek; Bakytzhan, Shynar (Millah: Journal of Religious Studies, 2025)
There has always been a fundamental tension between Islam and secularism, as well as between Islam and nationalism, during the critical early stages of nation and state-building in the modern Islamic world. Kazakhstan is no exception in this regard. As the Kazakh state reconstructs a secular national identity while facing a growing Muslim population, it faces the same challenges of negotiating the relationship between Islam and secularism and reconciling Islam with its secular governance model as other nations. In the post-Soviet context, Islam is not merely a localized socio-cultural phenomenon but is increasingly interconnected with global Islamic movements. This dynamic often creates friction with local traditions and official nation-building policies. This paper analyzes the interplay between Islam, securitization, and secularism in post-Soviet Kazakhstan and their impact on the implementation of restrictive policies toward religion. Through discourse analysis, this study examines how Islamic revival is framed as a security concern and how this framing informs restrictive state policies. It argues that securitization reinforces assertive secularism by narrowing the scope of acceptable religious expression and legitimizing expanded state control. Drawing on policy documents, media narratives, and scholarly discourse, the research highlights the historical and political legacies that continue to shape Kazakhstan’s approach to religion. The study calls for a more nuanced policy framework that distinguishes between ideological extremism and legitimate religious practice, ensuring both national security and freedom of belief.